1994
DOI: 10.1063/1.467266
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-infrared spectra of the Si2, Ge2, and Sn2 molecules in rare-gas matrices

Abstract: Absorption spectra of Si2, Ge2, and Sn2, observed between 50 and 5000 cm−1 in neon and argon matrices at 4 K, were assigned to the lowest 3Πu←X 3Σg− electronic transition. In all three cases, the Franck–Condon envelope of vibrational bands allowed T00, ωe′, ωe′xe′ to be determined. In the Si2 molecule [near Case (a)] T00=313 cm−1 and each vibrational band was split into Ω triplets (0,1,2) in the upper state. A Zeeman effect on these lines was detected in magnetic fields up to 4 T. As the spin–orbit coupling be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 38 publications
6
39
0
Order By: Relevance
“…The most stable structures for Si n clusters verified by theoretical methods [1][2][3][4][5][6][7] and experimental schemes [8][9][10][11][12][13][14][15], such as anion photoelectron spectroscopy [8][9][10][11][12] or Raman [13] and infrared measurements [14,15], are line for Si 2 , isosceles triangle for Si 3 , rhombus geometry for Si 4 , trigonal bipyramid for Si 5 , tetragonal bipyramid for Si 6 , pentagonal bipyramid for Si 7 . Although the predicted lowest-energy ground states for larger cluster were found to be dependent on the type of the calculation and also on the optimization technique [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most stable structures for Si n clusters verified by theoretical methods [1][2][3][4][5][6][7] and experimental schemes [8][9][10][11][12][13][14][15], such as anion photoelectron spectroscopy [8][9][10][11][12] or Raman [13] and infrared measurements [14,15], are line for Si 2 , isosceles triangle for Si 3 , rhombus geometry for Si 4 , trigonal bipyramid for Si 5 , tetragonal bipyramid for Si 6 , pentagonal bipyramid for Si 7 . Although the predicted lowest-energy ground states for larger cluster were found to be dependent on the type of the calculation and also on the optimization technique [16].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon clusters have been studied both experimentally and theoretically because of their intrinsic interest from the point of view of chemical structure and bonding as well as for their importance in the microelectronics industry [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The most stable structures for Si n clusters verified by theoretical methods [1][2][3][4][5][6][7] and experimental schemes [8][9][10][11][12][13][14][15], such as anion photoelectron spectroscopy [8][9][10][11][12] or Raman [13] and infrared measurements [14,15], are line for Si 2 , isosceles triangle for Si 3 , rhombus geometry for Si 4 , trigonal bipyramid for Si 5 , tetragonal bipyramid for Si 6 , pentagonal bipyramid for Si 7 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Neumark and co-workers [8][9][10][11][12] have used the negative ion zero-electron kinetic photodetachment spectroscopic techniques to study the electronic states of the neutral group IV and group III-V clusters. Weltner and co-workers [13][14][15] have studied matrix-isolated electron-spinresonance (ESR) spectra of small clusters of Ga, Si, Sn, and mixed group III-V elements. By using laser vaporization techniques, the infrared absorption spectra of GaX and InX (X) P, As, Sb) molecules in rare-gas matrices have been observed by Li et al 15,16 Although a large number of studies have been reported for the electronic structure and spectroscopic properties of GaAs, there seems to have a very little data on the isovalent GaBi molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[5] 0.11 *** 308 Exp. [1] 0.09 *** 308 Theoretical studies on singlet and triplet states of Ge 2 3259 Figure 7. Improved potential curves for selected states of Ge 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In a matrix absorption experiment, Li et al [1] observed the ground state (GS) of Ge 2 to be X 3 AE À g , with the 1 3 Å u state lying only 694 cm À1 (0.086 eV) higher. The GS of isovalent Si 2 is also X 3 AE À g , and 3 Å u lies 0.08 eV higher [2], but C 2 has an X 1 AE þ g (1p u 4 ) GS, with 3 Å u 0.09 eV, and 3 AE À g 0.80 eV higher [3].…”
Section: Introductionmentioning
confidence: 98%